THE ROLE OF THE MOSQUE IN ESTABLISHING PEACE OF COMMUNITY AFFECTED BY DISASTER AFFECTS (CASE STUDY OF MOSQUES IN PALU CITY) - Muhsin Muhsin (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2022)
This paper wants to show that mosques can help peace of mind for people affected by disasters. Many people who are affected by disasters, especially Muslims, when natural disasters occur, many run to the mosque. This phenomenon is very worthy of research and this happened in the city of Palu. In this study the author has also compared several other works with the author's writings including, first, Muhadi's work with the title Mosque as a Da'wah Center, and secondly Nurul Jannah's work with the title Revitalizing the Role of Mosques in the Modern Era (Case Study of Medan City), third, there is also M Syafi's work entitled Building Mosques at the Time of the Prophet and Its Implications for Women's Mosque Congregations, Fourth Mosque-Based Community Education by Suhairi Umar and fifth a journal article entitled